GENERAL DESCRIPTION OF PUBLIC KNOWLEDGE ABOUT SKIN DISEASES IN THE BELAWAN COASTAL AREA - Nurhayati, Nurhayati; Fadillah, Naya Kurnia; Aprida, Rahma; Nazwa, Aqila; Siregar, Algi Falah (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Skin diseases are a significant health problem worldwide, including Indonesia, with a higher prevalence in developing countries. This study aims to explore the picture of public knowledge regarding the high incidence of skin diseases in the coastal area of Belawan, Medan City. The method used was a quantitative study with a cross-sectional design, involving 70 respondents from the local community. The results showed that more than 50% of respondents had sufficient knowledge about skin diseases, although there were still groups who did not understand this condition, especially residents who work as fishermen aged 41-50 years. Knowledge about the prevention and treatment of skin diseases is closely related to healthy living behavior, where education is an important factor in increasing public awareness. In addition, easy access to information through technology and health education has been shown to contribute to improving individual understanding of skin diseases. Therefore, collaboration between the government, health institutions, and communities is needed to provide accurate and easily accessible information. A more educated community will be better able to maintain their skin health and reduce the prevalence of skin diseases in their environment. This study emphasizes the importance of increasing knowledge and access to information as a strategic step in efforts to prevent skin diseases in coastal areas.